Gender differences in public speaking anxiety of Filipino high school students from selected schools - De Leon, Miren B.; Flores, Romana S. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2001)
The study investigated the effect of gender (independent variable) on public speaking anxiety of PSA (dependent variable). It sought to find out if the cofounding variables of sex-segregated/coeducational class and the acquisition of language as first/second language have a significant influence on male and female PSA levels. The hypothesis of the study were: (1) Females manifest higher level of public speaking apprehension than males. (2) The sex-segregated/coeducational class does not affect the level of public speaking anxiety of the students. (3) Whether English language is their first or second language, such language affects the students' level of public speaking anxiety. McCroskey's Personal Report of Public Speaking Apprehension (PRPSA) was used to measure the anxiety level of high school students from Poveda (exclusive girls school), LA Salle Green Hills (exclusive boys school) and OB Montessori (coeducational school). Findings of the study proved the first and third hypothesis true. It showed that gender and the use of English as first or second language affect the level of public speaking anxiety in students.
Thesis (Bachelor of Arts in Speech Communication)--University of the Philippines Diliman
Keywords: Speech anxiety